2021
DOI: 10.3390/magnetochemistry7080109
|View full text |Cite
|
Sign up to set email alerts
|

Redox Activity as a Powerful Strategy to Tune Magnetic and/or Conducting Properties in Benzoquinone-Based Metal-Organic Frameworks

Abstract: Multifunctional molecular materials have attracted material scientists for several years as they are promising materials for the future generation of electronic devices. Careful selection of their molecular building blocks allows for the combination and/or even interplay of different physical properties in the same crystal lattice. Incorporation of redox activity in these networks is one of the most appealing and recent synthetic strategies used to enhance magnetic and/or conducting and/or optical properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…The perspective article by M. L. Mercuri et al at the University of Cagliari (Italy) and S. A. Sahadevan at the Royal Institute of Technology at Stockholm (Sweden), ref. [20], presents a review of coordination networks incorporating redox activity to enhance the magnetic, conducting and optical properties of these lattices. The contribution reviews the compounds prepared with quinone derivatives as redox-active linkers, since they have been widely used for electrode materials, flow batteries, pseudo-capacitors and other applications, thanks to the reversible two-electron redox reaction to form hydroquinone dianions via intermediate semiquinone radicals.…”
Section: Editorialmentioning
confidence: 99%
“…The perspective article by M. L. Mercuri et al at the University of Cagliari (Italy) and S. A. Sahadevan at the Royal Institute of Technology at Stockholm (Sweden), ref. [20], presents a review of coordination networks incorporating redox activity to enhance the magnetic, conducting and optical properties of these lattices. The contribution reviews the compounds prepared with quinone derivatives as redox-active linkers, since they have been widely used for electrode materials, flow batteries, pseudo-capacitors and other applications, thanks to the reversible two-electron redox reaction to form hydroquinone dianions via intermediate semiquinone radicals.…”
Section: Editorialmentioning
confidence: 99%
“…21 Additionally, redoxactivity of the benzoquinone core has been shown to be a challenging strategy to tune (enhancing) magnetism and conductivity in benzoquinone-based 3D/2D frameworks and related nanostructures. 22,23 Interestingly, Pontilliart et al reported the rst simultaneous reversible redox-and solvato-magnetic switching, observed in a dinuclear Dy III single-molecule magnet (SMM) complex based on a tetrathiafulvalene triad, through a reversible dehydration/rehydration process of the Dy III coordination sphere. Redox-activity plays a crucial role in the modulation of the Dy III magnetic relaxion through the addition of one water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews are reported on CPs and MOFs formed by redox-active linkers and nodes, 26,71–76 evidencing the crucial role of redox-activity on their physical properties and applications. The present review covers up new insights on benzoquinones (BQ)-based 2D CPs/MOFs and nanostructures over the last decade, highlighting the extreme versatility of this class of redox-active linkers in tailoring the physical properties of 2D frameworks and the related applications.…”
Section: Introductionmentioning
confidence: 99%